(untitled) (Conferencea, 2023)
The presidential election is a very relevant topic in the political life of our country. Because the elections and the constitutional procedure for conducting them are directly related to the degree of legitimacy of the president and the limit of competences. In addition, the elections held in the country are the only and best way to realize the most important political right of a person, the right to vote. Among the elections held in democratic countries, the presidential election is particularly important, during which the state body is formed, and the president takes office after taking the oath. Accordingly, "the president represents not only the body of the state government, but also the position." Direct elections were legalized shortly after the introduction of this institution as a method of holding presidential elections, which was in effect for years and had a significant impact on determining the quality of the president’s legitimacy and competences.